A computational model to determine the optimal orientation for solar greenhouses located at different latitudes in China. (1st May 2018) - Chen, Chao; Li, Yin; Li, Na; Wei, Shen; Yang, Fengguang; Ling, Haoshu; Yu, Nan; Han, Fengtao
Highlights: A study about factors influencing solar energy received by solar greenhouses. An optimal orientation model based on extreme value theory was developed. Model validation was carried out using both simulation and field measured data. A model guiding orientation for solar greenhouses at different latitudes in China. Abstract: The orientation of solar greenhouses has a significant impact on the ability of the solar radiation energy received by the south pitched roof. In this study, based on the law of the solar trajectory and the theory of heat balance, the calculation model of the opening and closing time of the thermal insulation curtain for the south pitched roof of solar greenhouses in different latitudes is given. Using Extreme Value Theory, a method that can be used to determine the optimal orientation for solar greenhouses, i.e. to maximize the solar energy collection, has been proposed, with a consideration of impact from geographical latitude. To validate the proposed method, both simulation data (by EnergyPlus) and field measured data have been used and a good agreement has been observed. The model has been implemented to predict optimal orientations of solar greenhouse located at nine different regions, where solar greenhouses are mainly used in the northern China.